Attitude and Knowledge towards COVID-19 Vaccination among Women in Chattogram, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: The COVID-19 pandemic is changing rapidly and requires different strategies to maintain clinical preventive services, including immunization. The authorized vaccines have shown to prevent severe illness and hospitalization from - COVID-19. However, knowledge and attitudes towards COVID 19 vaccinations among female populations are poorly understood. Thus, the study aimed to investigate knowledge and attitude towards COVID19 vaccinations in Bangladeshi women.Materials and methods: A cross-sectional study was performed in Chittagong Medical College Hospital, Chattogram from 14 February to 16 February 2021. The study was conducted using a structured, pre-formed questionnaire containing informed written consent along with three sections, i.e. sociodemographic profile, knowledge and attitudes. All women who had come to take vaccine against COVID- 19 in this hospital during the study period were the study population. Women who were not agreed to take part in the study and having complications e.g. mental disorder, hearing difficulty or critically ill were excluded from the study. The final sample size was 225. Systematic random sampling was applied to select the study population.Results: During the study, 43% cases belong to 40-49 years’ age group and 91% were from urban area. Regarding knowledge towards vaccination, 69% study group think vaccine can give complete protection from COVID-19 and 97% cases have knowledge that vaccine can reduce severity of COVID-19 but 6% didn’t sure about death cases from vaccination, 51% shows positive results regarding elder people are at high risk from vaccination than younger, 79% study group think people with comorbid diseases are at high risk from vaccination. Regarding attitude towards vaccination, 95% cases were taking their vaccine willingly followed by 2% women think vaccine may not effective against COVID-19, 12% think rich people need vaccine more than poor.Conclusion: The COVID-19 pandemic is still experiencing worldwide disasters but a possible ray of hope for the future can be found with the COVID-19 vaccine. The findings recommend that immediate programs of health education and the respective health authorities should provide more accurate information. In order to decrease vaccine relief enabled and promoted by disinformation in the media, policymakers should take efforts to provide appropriate understanding, favorable attitudes and views of COVID-19 immunization.Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 26-30